Model Laboratorium Lapangan Identifikasi Limbah Cair Menggunakan Metode Cross-Hole Geolistrik Resistivitas - Reza Devianta; Budi Legowo; Hery Purwanto (Department of Physics, Sebelas Maret University, 2016)
It has been done a cross-hole method of field laboratory geoelectrical resistivity to identify the wastewater in Grogol, Gatak, Delanggu, Jawa Tengah. Measurements were performed using McOHM 2119C-EL OYO Resistivity meter. The Anomaly of the object that has given of this research is wastewater. The data acquisition of cross-hole model use dipole-dipole geoelectrical configuration. The distance between the two boreholes is 3 m and spaced electrodes that used are 0,1 m; 0,2 m; 0,3 m and 0,4 m. The Data will be taken from the movement of saline water anomaly that mobiles on the ground and each taking every 4 days for 5 times of the data acquisition. A description of the result of the anomaly will be reviewed using RES2DINV 3.56software. The visualization of the movement of wastewater model on day 4th is at a depth of 0,4 m – 0,6 m at a distance x = 0,5 m - 2,5 m with resistivity 10 - 10,8 Ωm. On day 8th is located at a depth x = 0,5 m – 0,8 m, x = 0,5 m – 2,5 m with resistivity 10 - 14 Ωm. And on day 12th is located at a depth of 0,8 m – 1,2 m at a distance x = 0 m – 0,5 m, x = 2,5 m - 3,0 m and x =1,5m - 2,5 m with a resistivity of 12,4 - 15 Ωm.